Brief Yoga Intervention for Dental and Dental Hygiene Students: A Feasibility and Acceptability Study - Sarah Ellen Braun MS; George Deeb DDS, MD, FACS; Caroline Carrico PhD; Patricia A. Kinser PhD, WHNP-BC, RN, FNAP (SAGE Publishing, 2019)
The present study investigated whether a brief yoga intervention would be feasible and acceptable for dental students. Based on empirical evidence about state mindfulness (SM), change in self-reported SM was assessed as a measure of the intervention's feasibility and acceptability. A repeated-measures within-subjects design was used. Participants were third- and fourth-year dental and dental hygiene students (76% female). The State Mindfulness Scale (SMS), a validated self-report measure of SM with 2 subscales, Mind and Body, was used. Students (n = 132) completed the SMS immediately prior to and following a 1-hour yoga intervention. Dispositional mindfulness, burnout, perceived stress, and depressive symptoms were also investigated as moderators of changes in state mindfulness to determine whether psychological variables had an effect on feasibility in this sample. Total SM significantly increased from pre- to post-intervention, t (46) = 10.26, P < .001. An analysis of covariance showed a significant interaction effect in the relationship between pre-/post-intervention SM of Mind ( β = 0.51, P = .048), such that higher levels of stress saw greater increases in SM of Mind. No other psychological variables were significant moderators. A brief yoga intervention for dental students significantly increased SM, suggesting that yoga interventions may be feasible and acceptable in this population. The results of moderation analyses suggest that a brief yoga intervention may be especially effective at increasing SM for those with high levels of stress. Future research should use a randomized control group to test group differences in SM after a brief yoga intervention for dental students.